Facial Paresthesia, a Rare Manifestation of Hereditary Neuropathy With Liability to Pressure Palsies: A Case Report - De Kock, Lisa; Van der Cruyssen, Fréderic; Gruijthuijsen, Leonore; Politis, Constantinus (Frontiers in Neurology, 2021)
Trigeminal sensory neuropathy can be caused by a variety of conditions, including local, traumatic, iatrogenic, or systemic causes. Diagnosis and management remain a challenge for maxillofacial surgeons and neurologists. Therefore, a good clinical examination and objective tests and imaging are needed when diagnosing patients who present with facial numbness. We present a case with spontaneous episodes of facial paresthesia. He was diagnosed with hereditary neuropathy with liability to pressure palsies (HNPP), a rare condition that affects the peripheral nerves. Only a few case reports that describe involvement of the cranial nerves in patients with HNPP were found in the literature, and facial paresthesia has not been previously reported.